Design Thinking Methodology for the Development of Creativity of University Audiovisual Students - Ventocilla Maestre, José Ernesto (2024)
Audiovisual production comprises several stages and faces different problems in which it must be oriented to established processes, or create them by opting for original solutions. In view of this, the methodology called Design thinking was taken into account to develop the creativity of the process. A study was carried out with a mixed holistic approach, a quantitative pre- and post-test design, and for the qualitative Action Research; This was applied in two audiovisual subjects throughout the 2023 school year, with 40 students in each cycle, thus making up the sample and the study universe, divided into 4 experimental groups and 3 control groups. The results indicated that there was no significance in the application of Design thinking in the development of creativity, but it is concluded at the same time that there was a development in the synergies of creativity contained in the development of the students' project.